Origins of the Latin American Nationalist Media Discourse - Goshkina, Yuliya (European Journal of Social Science Education and Research, 2018)
The article deals with the process of formation, development, and manifestation of the distinctive features of a phenomenon called Latin American nationalism and its reflections in the local print media. This theme was chosen because of author’s scientific interests related to the study of the nationalist media discourse and specific strategies of political communication presented in contemporary Latin America. In this paper, the author analyzes causes of Latin American nationalism of historical, philosophical and geopolitical positions, describes the process of its gradual transformation and names its standard markers.